Guest Editors' Introduction: Multimedia Metadata and Semantic Management - Chbeir, Richard; Kosch, Harald; Andres, Frederic; Ishikawa, Hiroshi (IEEE Multimedia, 2009)
This special issue assesses the current status and technologies and describes major challenges and proper solutions for effective multimedia production and management related to evolving Semantic Web strategies. The included articles, which cover different facets of the semantic management of multimedia and multimedia metadata from retrieval and processing to consumption and presentation, represent a step forward in research targeted at improving aspects of the semantic metadata life cycle.